State political identity and meta-governance: Comparative analysis of governance modes in vegetable retail in urban China - ZHANG, Qian Forrest (Institutional Knowledge at Singapore Management University, 2015)
A government's political identity is a key factor in meta-governance; it powerfully shapes a government's policy aims and implementation preferences at the most abstract level and forms a stable governance mode. Dissonance between a pre-existing governance mode and the government's evolved political identity will lead to governance failures and pose political challenges to the government. In the case of vegetable retail in Shanghai, the neoliberal developmental state transformed the hierarchical governance into market governance; but as it evolves into a corporatist welfare state, market imperfections come to be perceived as governance failures, and the government responds by reintroducing hierarchical measures.